Potential of Marine Sponge-Associated Fungi (Callyspongia sp.) as Textile Dye Biodegradation Agents - Erlita Dwi Octaviani; Agus Trianto; Ocky Karna Radjasa; Bambang Yulianto; Agus Sabdono; Erin M. Cauley (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2025)
Textile industries generate large volumes of wastewater containing synthetic dyes such as azo, naphthol, and rhodamine B, which are highly resistant to degradation and pose significant environmental risks when discharged into aquatic ecosystems. These dyes can be toxic to aquatic life, disrupt food chains, and cause long-term pollution. This study aimed to evaluate the biodegradation potential of marine fungi isolated from the sponge Callyspongia sp. as a natural and eco-friendly solution for textile dye removal. Two fungal isolates, RA.S12.1 and RA.S12.2, were tested on solid and liquid media with 200 ppm dye concentrations. Isolation involved collecting sponges from marine environments and culturing them on selective media to obtain fungal colonies. Decolorization was assessed through qualitative observations (changes in growth zone color) and quantitative analyses using UV-Vis spectrophotometry to measure absorbance reductions at specific wavelengths, as well as CMYK color measurements to quantify objective color intensity changes. Results indicated that isolate RA.S12.2 achieved the highest decolorization percentage of 64.8% for Azo Mordant Black 17 after 7 days of incubation, while RA.S12.1 reached only 30.1%. Molecular identification via ITS rDNA gene sequencing confirmed both isolates as Penicillium citrinum with 100% homology. These findings suggest that marine-derived P. citrinum holds strong potential as a bioremediation agent for textile dye degradation, offering an environmentally friendly alternative for wastewater treatment in coastal and marine areas impacted by industrial pollution. This approach could provide a sustainable alternative to conventional chemical methods, with broader applications in mitigating global aquatic pollution. Further research is needed to optimize conditions and test at an industrial scale.